Zooplankton sampling during the 57th Japanese Antarctic Research Expedition in austral summer 2015–2016 - TAKAHASHI, Kunio T.; TAKAMURA, Tomomi R.; MAKABE, Ryusuke; ODATE, Tsuneo (国立極地研究所, 2016)
Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0027.docx Fig. 2 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0028.docx Fig. 3 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0029.docx Fig. 4 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0030.docx Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0031.doc Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0032.doc Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0033.doc Table 4 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0034.doc Table 5 | http://polaris.nipr.ac.jp/~parc/pub/v024/nipr_parc_175_0035.doc departmental bulletin paper